The Bruker AXS SMART CCD: Technology Analysis Crystal Structure of Bis (trimethyltin) croconate [(CH3)3Sn]2C5O 2H2O - Asrial Asrial; Haryanto Haryanto; Asmiyunda Asmiyunda (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to synthesize and characterize a novel organotin oxocarbon complex, namely bis(trimethyltin) croconate dihydrate [(CH₃)₃Sn]₂C₅O₅·2H₂O, and to investigate its molecular geometry, coordination behavior, supramolecular arrangement, and spectroscopic properties. Methodology: The compound was synthesized through a solution reaction between sodium croconate and trimethyltin chloride under atmospheric conditions at room temperature. Structural characterization was conducted using single-crystal X-ray diffraction analysis with a Bruker AXS SMART CCD-System diffractometer and refined using the SHELXS-97 software package. Additional characterization techniques included FTIR spectroscopy, CHN elemental analysis, and ¹H- and ¹³C-NMR spectroscopy. Main Findings: The synthesized compound crystallized in the orthorhombic system with the Fddd space group and formed bright yellow needle-shaped crystals. Structural analysis revealed that the croconate dianion acts as a bidentate bridging ligand connecting two trimethyltin groups. Each tin atom exhibits pentacoordination with distorted trigonal bipyramidal geometry. Bond length analysis confirmed π-electron delocalization within the croconate ring, indicating aromatic character. Hydrogen bonding interactions between coordinated water molecules and croconate oxygen atoms generated an extended supramolecular network. FTIR and NMR spectra further supported the formation of the target complex, while elemental analysis confirmed agreement between theoretical and experimental compositions. Novelty/Originality of this study: This study reports the successful synthesis and comprehensive crystallographic characterization of bis(trimethyltin) croconate dihydrate, a croconate-based organotin complex that has rarely been explored. The research provides new insights into the coordination behavior of croconate ligands toward trimethyltin centers, the formation of hydrogen-bonded supramolecular structures, and the role of π-electron delocalization in stabilizing organotin oxocarbon frameworks.